Risk of Getting COVID-19 in People With Multiple Sclerosis: A Case-Control Study. Issue 2 (19th March 2022) - Iaffaldano, Pietro; Lucisano, Giuseppe; Manni, Alessia; Paolicelli, Damiano; Patti, Francesco; Capobianco, Marco; Brescia Morra, Vincenzo; Sola, Patrizia; Pesci, Ilaria; Lus, Giacomo; De Luca, Giovanna; Lugaresi, Alessandra; et al.
Abstract : Background and Objectives: Several studies have assessed risk factors associated with the severity of COVID-19 outcomes in people with multiple sclerosis (PwMS). The potential role of disease-modifying therapies (DMTs) and demographic and clinical factors on the risk of acquiring SARS-CoV-2 infection has not been evaluated so far. The objective of this study was to assess risk factors of contracting SARS-CoV-2 infection in PwMS by using data collected in the Italian MS Register (IMSR). Methods: A case-control (1:2) study was set up. Cases included PwMS with a confirmed diagnosis of COVID-19, and controls included PwMS without a confirmed diagnosis of COVID-19. Both groups were propensity score–matched by the date of COVID-19 diagnosis, the date of last visit, and the region of residence. No healthy controls were included in this study. COVID-19 risk was estimated by multivariable logistic regression models including demographic and clinical covariates. The impact of DMTs was assessed in 3 independent logistic regression models including one of the following covariates: last administered DMT, previous DMT sequences, or the place where the last treatment was administered. Results: A total of 779 PwMS with confirmed COVID-19 (cases) were matched to 1, 558 PwMS without COVID-19 (controls). In all 3 models, comorbidities, female sex, and a younger age were significantly associated ( p < 0.02) with a higher risk of contracting COVID-19. Patients receiving natalizumab as last DMT (OR [95% CI]: 2.38 [1.66–3.42], p < 0.0001) and those who underwent an escalation treatment strategy (1.57 [1.16–2.13], p = 0.003) were at significantly higher COVID-19 risk. Moreover, PwMS receiving their last DMT requiring hospital access (1.65 [1.34–2.04], p < 0.0001) showed a significant higher risk than those taking self-administered DMTs at home. Discussion: This case-control study embedded in the IMSR showed that PwMS at higher COVID-19 risk are younger, more frequently female individuals, and with comorbidities. Long-lasting escalation approach and last therapies that expose patients to the hospital environment seem to significantly increase the risk of SARS-CoV2 infection in PwMS. Classification of Evidence: This study provides Class III evidence that among patients with MS, younger age, being female individuals, having more comorbidities, receiving natalizumab, undergoing an escalating treatment strategy, or receiving treatment at a hospital were associated with being infected with COVID-19. Among patients with MS who were infected with COVID-19, a severe course was associated with increasing age and having a progressive form of MS, whereas not being on treatment or receiving an interferon beta agent was protective.